PERENCANAAN KEUANGAN KELUARGA MELALUI OPTIMALISASI KOMPOSISI INVESTASI PADA TABUNGAN, ASURANSI DAN REKSADANA BERDASAR PRIORITAS TUJUAN - Puspharini, Lia Anitha; Hidayati, Cholis (Universitas 17 Agustus 1945 Surabaya, 2016)
Financial Planning is a profession that helps families to plan the family finances by identifying and analyzing the financial goals and problems as well as providing solutions so that the proper short, medium and long term goals can be achieved. This Financial planning is done to a client named Mr. Djoko Slamet Sunarto as the owner of PT. Mukti Sejahtera Mulia engaged in contracting services. The client has moderate aggressive risk profile, which means He wants a high investment result although it contains some risks and quite high volatality as well. The client’s assets currently contain current assets 11.89 percent, 57.39 percent of investment or fixed assets and the assets of the private usage of 30.72 percent. The Client's financial goals ia the availability of having an emergency fund, life and health insurance, the second child marriages funds and pension funds. Financial planning is done in several stages. The initial meeting was charging data and interviews. The analysis conducted in this study was qualitative and quantitative. While the methods of financial planning is done by identifying the client ; setting goals and getting the data; analysis and evaluation of the client's financial status; presenting the financial planning recommendations. Sources of funds used to meet the objectives were that the emergency funds will be taken from the assets, while the life and health insurance and child marriages funds will be taken from disposable income. Special to the pension fund, it will be taken both from of assets and disposable income. After analysis and discussion, it can be concluded that in order to achieve the client’s goals, It recommended that some financial products could be conformly used, namely : the Savings Mandiri, BNI-AM Dana Liquid, Danamas Dollar, Simas One, and HPAM Ultima EquityKeywords: Financial Planning, Savings, Insurance, Mutual Funds